High efficacy in hyperthermia-associated with polyphosphate magnetic nanoparticles for oral cancer treatment - Candido, N. M. [UNESP]; Calmon, Marilia de Freitas [UNESP]; Taboga, Sebastião Roberto [UNESP]; Bonilha, Jane Lopes; dos Santos, M. C.; Lima, Emilia Celma de Oliveira; Sousa, C. R. S.; Lacava, Zulmira Guerrero Marques; Rahal, Paula [UNESP] (OMICS International, 2014)
Nanotherapy applied to cancer treatment is constantly evolving, and new approaches to current techniques, such as magnetohyperthermia, are being implemented to solve and minimize the limitations of conventional therapeutic strategies. The purpose of this study was to investigate the action of polyphosphate-coated maghemite nanoparticles (MNPs) on oral squamous cell carcinoma. Human oral cancer cells (UM-SCC14A) were incubated with MNPs at various concentrations and subjected to cell proliferation tests (MTT), apoptosis assays and transmission electron image analysis. Viability and apoptotic events were time and dose dependent. These in vitro tests showed that at the intermediate concentration tested there is no significant toxicity, as confirmed by transmission electron microscopy. For this reason this MNPs concentration was chosen for the subsequent in vivo tests. Oral tumor induction was performed by applying the carcinogen DMBA to Syrian hamsters. Animals were then treated by magnetohyperthermia using MNPs. No signs of general clinical symptoms of toxicity or abnormal behavioral reactions were observed. However, animals treated with MNPs and exposed to the alternating magnetic field in the hyperthermia procedure exhibited a significant and time dependent cancer regression, as confirmed by histopathological analyses and immunohistochemistry. Actually, in quantitative terms of the magnetotherapy efficacy involving these polyphosphate-coated MNPs, 100% recovery (12/12) was observed in the oral cancer tumor bearing Syrian hamsters seven days after the treatment with the magnetohyperthermia procedure. Data supports the suggestion that the MNPs-mediated hyperthermia represents a promising strategy for the treatment of oral cancer.
Keywords: Oral squamous cell carcinoma; UM-SCC14A; Syrian hamster; Magnetic nanoparticles coated with polyphosphate; Magnetohyperthermia